Headache A Symptom not a Disease - Mohammad, QD (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Headache is a ubiquitous symptom, yet it is one that often elicits anxiety in both patients and physicians. No symptom more than headache gives a physician the chance to regain the time-honored role of healer. Most primary headache can be managed in primary care and investigations are rarely needed. When a patient presents with headache, the clinician must answer the following questions: (1) Is the headache worrisome (secondary to underlying disease)? (2) If the headache is benign, what type is it? (3) How is headache best treated ? Every presentation of headache requires care to exclude organic disease, and every presentation provides the opportunity to relieve suffering. The following review is intended to aid physicians in answering these questions. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21005 J Bangladesh Coll Phys Surg 2013; 31: 204-208